2014
DOI: 10.1002/hbm.22633
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the connectome in schizophrenia with diffusion spectrum imaging

Abstract: Schizophrenia is a complex psychiatric disorder characterized by disabling symptoms and cognitive deficit. Recent neuroimaging findings suggest that large parts of the brain are affected by the disease, and that the capacity of functional integration between brain areas is decreased. In this study we questioned (i) which brain areas underlie the loss of network integration properties observed in the pathology, (ii) what is the topological role of the affected regions within the overall brain network and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
62
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 90 publications
14
62
1
3
Order By: Relevance
“…Also, it is important to consider that our simulations assumed no structural differences between groups and instead generated predictions based on functional parameters. Given possible interareal anatomical connectivity alteration in chronic SCZ patients (99), future work that uses whole-brain probabilistic tractography approaches (100) will be key to generate appropriate modeling constraints across groups to improve model fits.…”
Section: The Interplay Of Biophysically Based Computational Modeling Andmentioning
confidence: 99%
“…Also, it is important to consider that our simulations assumed no structural differences between groups and instead generated predictions based on functional parameters. Given possible interareal anatomical connectivity alteration in chronic SCZ patients (99), future work that uses whole-brain probabilistic tractography approaches (100) will be key to generate appropriate modeling constraints across groups to improve model fits.…”
Section: The Interplay Of Biophysically Based Computational Modeling Andmentioning
confidence: 99%
“…DSI is another related technique aimed at clearly mapping regions of crossing fibers, and which has been able to reveal entirely new features of the organization of the WM (125127). DSI has been only recently applied in schizophrenia, in investigations of the mirror neuron network (128), language networks (129), connectome based analyses (130), and a sibling study (128). Calculation of a permeability diffusivity index (PDI) that can putatively model more complex aspects of cellular microstructure has been used in schizophrenia, and found that membrane permeability is decreased in patients (131) and may be an important part of the accelerated aging observed in schizophrenia (132).…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…The brain connectome provides unprecedented information about global and regional conformations of neuronal network architecture. This information is particularly relevant as it relates to neurological or psychiatric disorders such as epilepsy (Richardson, 2012; Engel et al, 2013; Taylor et al, 2014), schizophrenia (Rubinov and Bullmore, 2013; Crossley et al, 2014; Griffa et al, 2015), and Alzheimer's disease (Xie and He, 2011; Daianu et al, 2013; Zhu et al, 2014), which are believed to be directly associated with restructuring of complex neuronal networks.…”
Section: Introductionmentioning
confidence: 99%